The functions of fluoxetine and identification of fluoxetine-mediated circular RNAs and messenger RNAs in cerebral ischemic stroke. Issue 1 (1st January 2021) - He, Yitao; Zhang, Hui; Deng, Jian; Cai, Zhili; Gu, Mei; Zhao, Chenyong; Guo, Yi
ABSTRACT: Fluoxetine is used to improve cognition, exercise ability, depression, and neurological functions in patients with cerebral ischemic stroke. Circular RNAs (circRNAs) play important regulatory roles in multiple diseases. However, studies regarding the fluoxetine-mediated circRNA–microRNA–messenger RNA (mRNA) axis have not been conducted. This study is aim to investigate the functions of fluoxetine and identification of fluoxetine-mediated circRNAs and mRNAs in cerebral ischemic stroke. The middle cerebral artery occlusion (MCAO) rat models were successfully established at fisrt, and then rats were intraperitoneally injected with 10-mg/kg fluoxetine hydrochloride for 14 d. Afterward, the cerebral infarction area was evaluated using triphenyltetrazolium chloride staining. High-throughput sequencing was adopted to screen the differential circRNAs and mRNAs. The candidate circRNAs, mRNAs, and potential microRNAs were verified using quantitative reverse transcriptase polymerase chain reaction (qRT-PCR). In addtion, microRNA and circRNA binding was verified using the dual-luciferase reporter assay. Results revealed that fluoxetine markedly diminished the cerebral infarction area in rats after MCAO. The circRNAs and mRNAs were differentially expressed, which includes 879 circRNAs and 815 mRNAs between sham and MCAO groups, respectively, and 958 circRNAs and 838 mRNAs between MCAO and fluoxetine groups, respectively. In which, circMap2k1 and Pidd1 expression was significantly increased in the MCAO group but suppressed after fluoxetine treatment. Moreover, circMap2k1 directly binds with miR-135b-5p. Taken together, we verified that fluoxetine could improve brain injury after cerebral ischemic stroke. Moreover, the circMap2k1/miR-135b-5p/Pidd1 axis is potentially involved in cerebral ischemic stroke. Graphical abstract: uf0001